Effect of Green-emitting CaF2:Ce3+,Tb3+ Phosphor Concentration on the Correlated Color Temperature Deviation and the Lumen Output of the 7700 K Conformal Packaging WLEDs (International Journal of Automation and Smart Technology, 2025)
In this manuscript, we propose a recommendation for improving the correlated color temperature deviation (D-CCT) and the lumen output of 7700 K WLEDs by adding the green-emitting CaF2:Ce3+,Tb3+ phosphor into the yellow- emitting YAG:Ce phosphor compounding. From the research results, the D-CCT could decrease more than 4 times, and the lumen output increased more than 1,5 times in comparison with the non-green-emitting CaF2:Ce3+,Tb3+ phosphor case. The results show that green-emitting CaF2:Ce3+,Tb3+ phosphor could become a new recommendation for enhancing the D-CCT and the lumen output of WLEDs.